Parachordoma: a rare recurring case at a rare site - Vernekar, Sunita S.; Patil, Ankitha; Giriyan, Sujata S. (International Journal of Research in Medical Sciences, 2020)
Parachordoma is an uncommon tumor of soft tissue and the orign is not clear. This soft tissue tumor resembles chordomas as well as extraskeletal myxoid chondrosarcomas and has only recently been fully characterized. Although it is considered a benign lesion, its behavior tends to be locally aggressive, with reports of a recurrence rate of up to 20% and of several cases of metastasis. In this article, we report a case of parachordoma in the neck with recurrence that we met in clinical works.